Do Bush Control Techniques Have an Effect on the Density, Cover and Recruitment of Woody Plants in a Semi-Arid Savanna? The Case of a Semi-Arid Savanna, Southern Ethiopia - Hare, Malicha L.; Wang, Yong D.; Xu, Xin W.; Yuan, You; Na, Zhou; Gedda, Abule E. (Frontiers in Environmental Science, 2021)
High bush density and cover have negative effects on the environment in general and on livestock production in particular in savanna rangelands. The study examined the effects of bush control techniques on woody sapling recruitment in the low land savanna region. The study consisted of 21 plots located next to each other on an area of 5.3 hectares encroached by A. mellifera and A. reficiens trees. Seven bush control treatments were assigned randomly to the plots and replicated three times. In the bush clearing plot, woody species were removed at ground level using a handsaw. In the tree thinning; thinning and grazing; thinning and browsing; thinning and fire, and thinning with fire-browsing treatments, trees were thinned to the equivalents of 60% of the density of that of the control plot. Positive changes in saplings densities were observed in the clearing, thinning, and thinning and grazing treatments. In contrast, the control, thinning and browsing, and thinning and fire treatments presented negative changes in densities. A change in sapling density was highest in the cleared plot, while was lowest in the thinning, fire and browsing treatment. The correlation between changes in sapling densities and new recruitments was highly (P < 0.001) significant in the clearing, thinning, and thinning and grazing treatments thus increased sapling recruitment with the proportion greater for the clearing treatment. The significant correlation induced average sapling recruitment in the control, and low in the thinning with browsing and thinning with fire treatments. The relationship was insignificant in the thinning, fire and browsing combination treatment and resulted in the lowest rate of saplings' recruitment. Post-thinning techniques reduced woody tree recruitment and would sustain open savanna under the continuous management plan. Keywords: bush control technique, woody plants, saplings, recruitment